Impact of hyperthyroidism on in-hospital outcomes of patients with heart failure - Kunjan Udani; Dveet Patel; Leslie Hart; Vinod Nambudiri (Greater Baltimore Medical Center, 2021)
Congestive heart failure (CHF) exacerbations are a frequent cause of hospitalization. Thyroid hormones impact myocardial function; elevated levels of thyroxine, as seen in hyperthyroidism (HT), can worsen CHF symptoms. We retrospectively evaluated the Hospital Corporation of America (HCA) Enterprise Data Warehouse and examined mortality and length of stay (LOS) in patients hospitalized with CHF with and without a diagnosis of HT. 55,031 patients with CHF were identified. The presence of HT was not significantly associated with mortality (p = 0.24) nor LOS (p = 0.32). A significant difference in the distribution of sex (p = 0.001) and age (p = 0.002) was noted, with a higher percentage of females and a lower median age in patients with HT. There was a significant difference in LOS (p = 0.04) for patients with a cardiovascular comorbidity, who had a mean LOS of 6.33 days versus 5.31 days for patient without HT.